Using Podcasts in EFL Classroom: Does It Affect Students’ Listening Comprehension? - ditha natalia binsasi (Universitas Muhammadiyah Tangerang, 2024)
Listening is an essential skill to develop, especially for second-language learners. It is regarded as one of the difficultÂ things to learn. This study investigates the usage of podcasts in the listening comprehension skills of EFL students. This research used a pre-experimental design with one group pre-test and post-test design on students at SMPN 229 Jakarta. The research sample consisted of 33 students in grade 9. The Wilcoxon sign rank test is used in the research as a quantitative way to assess data statistically. According to the findings, the usage of podcasts influences students' listening comprehension skills, with substantial statistical variations between the pre-test and post-test.